The role of CD154 in haematopoietic development - Seijkens, Tom; Engel, David; Tjwa, Marc; Lutgens, Esther (Thrombosis and Haemostasis, 2010)
CD154 (CD40 ligand, CD40L, gp139) is a co-stimulatory molecule of the tumour necrosis factor (TNF) family. CD154 was originally discovered on T-cells, and was found to be involved in many immune responses including B-cell activation, isotype switching, and germinal centre formation. The expression of CD154 on other haematopoietic and nonhaematopoietic cells suggests that CD154 has other functions as well. Indeed, CD154 is involved in many pathological processes, including inflammatory and autoimmune diseases. Genetic studies in patients and mice taught us that CD154 might affect haematopoietic stem and progenitor cells (HSPCs), T-cell, B-cell, and dendritic cell (DC) progenitors. Moreover, the development of specific T-cell and DC subsets critically depends on CD154. Furthermore, CD154 is involved in lymphoid malignancies. Here we highlight the role of CD154 in the developing lymphoid system, including the biology of HSPC and lineage-committed T-cell, B-cell, NK, and DC progenitors. Further, the clinical and therapeutic implications of CD154 interactions in lymphopoiesis will be discussed.
Keywords: CD154; CD40; haematopoiesis; lymphopoiesis